Iptek Untuk Kelompok Usaha Aneka Roti Dan Kue Di Bangka Belitung - Sukanto Sukanto; Zulfan Yus Andi; Yudi Oktriadi; Abdul Budi (Manutech : Jurnal Teknologi Manufaktur, 2016)
In recent days, the bread and cake for most Indonesian people have been used as a meal replacement or substitute for the staple food. Required good planning and management in order to meet the customer demand, the customer fulfillment both in quantity and in quality, especially in the operational management of production processes. These activities aimed to assist the partners in developing their business. The methods and procedures applied in the first stage is to survey the problems of the partners, the second stage of the design and analysis of alternative dispute resolution solutions partners. Furthermore, the third phase-grant program implemented as a solution to the problems faced by each partner. Service activities has been giving grants to the first partner in the form of mixer machine, oven, counter display case and the second partner giving grant heating chocolate machine and repair mixer machine with a capacity of 9 Kg. Besides the two partners are also given training related to maintenance machinery and entrepreneurship. This service activities have an impact on first partner is number of asset’s increased up to 2.7-fold, speeds production increased by two times and followed by an increasing number of customers, and product sale also increased by two times compared to the previous. While in both partners, this event has helped to produce the information concerning the identification of base problems so that it can be used as a reference for improved planning and management development efforts.